Multiple Sclerosis – An Ophthalmologist’s perspective - Reena Sharma; Rohit Saxena; Rohit Bhatia; Vimla Menon (Delhi Journal of Ophthalmology)
Multiple sclerosis is a nervous system disease that affects brain and spinal cord. It damages the myelin sheath, the material that surrounds and protects the nerve cells. Its symptoms are varied and unpredictable. It commonly affects the optic nerve and ocular movements. Up to 50% of patients with multiple sclerosis will develop an episode of optic neuritis, and 20-30% of the time optic neuritis is the presenting sign of multiple sclerosis. Optic neuritis is diagnosed clinically and followed up using visual acuity, colour vision, contrast sensitivity, visual fields, magnetic resonance imaging and optical coherence tomography. Bilateral internuclear ophthalmoplegia, abnormalities resulting from cerebellar damage or to its connections and pendular nystagmus are other common ophthalmic manifestations of the disease. Multiple sclerosis is diagnosed using McDonald criterion, based on the occurrence of at least two clinical episodes of neurological involvement separated in time and space. The magnetic resonance imaging aids the diagnosis and requires the presence of lesions in at least 2 of the four locations-periventricular, juxtacortical, infratentorial and spinal cord. The treatment of multiple sclerosis is multidisciplinary, invoving the treating physician, physiotherapists, occupational therapists, nurses and social workers. There are no drugs to cure multiple sclerosis, but several therapies are available that can ameliorate the symptoms of multiple sclerosis and, in some cases, slow the disease progression.